2023
DOI: 10.1519/jsc.0000000000004387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity vs. Moderate-Intensity Resistance Training on Strength, Power, and Muscle Soreness in Male Academy Soccer Players

Abstract: McQuilliam, SJ, Clark, DR, Erskine, RM, and Brownlee, TE. The effect of high vs. moderate-intensity resistance training on strength, power and muscle soreness in male academy soccer players. J Strength Cond Res 37(6): 1250–1258, 2023—The aims of this study were to investigate the impact of high-intensity, low-volume (HRT) vs. moderate-intensity, and high-volume resistance training (MRT) vs. soccer training only (control group [CON]) on changes in strength, power, and speed and to compare delayed onset muscle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…47 Furthermore, time restrictions have previously been cited as a major factor when looking to implement injury prevention strategies in soccer, 11 with 32% of coaches in our study stating that limited time restricted their practice. A low-volume, high-intensity strength training protocol (90% 1RM) has previously been implemented in-season with professional 48 and academy soccer players, 39 and may be a potential solution to alleviating these perceived restrictions. Strength development needs to be effectively implemented alongside training other physical components important to soccer performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Furthermore, time restrictions have previously been cited as a major factor when looking to implement injury prevention strategies in soccer, 11 with 32% of coaches in our study stating that limited time restricted their practice. A low-volume, high-intensity strength training protocol (90% 1RM) has previously been implemented in-season with professional 48 and academy soccer players, 39 and may be a potential solution to alleviating these perceived restrictions. Strength development needs to be effectively implemented alongside training other physical components important to soccer performance.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that highintensity (90% 1RM) strength training performed just once a week in-season had more performance benefits compared to moderate intensity (80% 1RM) strength training and soccer training only, with no difference in perceived muscle soreness. 39 Thus, it appears as though soccer players would indeed benefit from undertaking highintensity strength training as part of their weekly training, as recommended in the scientific guidelines. 38 It is commonly accepted that training intensity is a crucial factor when the aim is to increase an individual's strength.…”
Section: Discussionmentioning
confidence: 99%
“…Using RecyclerView's circular queue effectively reduces the performance burden caused by constantly breaking projects and creating new ones. At the same time, this method also stores the layout information of each item in this item, when an item is viewed, the layout information can be read from within it, thus reducing the performance burden caused by the need to load the layout again from the layout file for each item [16]. The software cannot determine whether it is a month view or a day view, or whether the viewer has received a scroll indication.…”
Section: B System Software Designmentioning
confidence: 99%